E-Module Development of Physical Education Subjects for Sports and Health on Physical Fitness Materials for Class VII Junior High School Students (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to develop an e-module for physical education subjects, sports and health on physical fitness material for seventh grade junior high school students. The type of research is research and development with the ADDIE development model (Analysis, Define, Development, Implementation and Evaluation). The research was conducted at SMP Negeri 23 Kerinci, SMP Negeri 10 Kerinci and SMP Negeri 19 Kerinci. is a validation sheet. Data collection techniques in the form of instruments that have been validated by experts. Data analysis techniques use validation sheets. Data analysis techniques use rating scales and percentage ranges. physical fitness for class VII junior high school students is very feasible to be used as teaching material with a validation value of 92.8%, 2) e-module product for physical education subjects, sports and health on physical fitness material for class VII junior high school students which was developed effectively for junior high school students class VII with the results of the effectiveness test of 76.8 > 76.